Effects of the PCM layer position on the comprehensive performance of a built-middle PV-Trombe wall system for building application in the heating season. (15th March 2023) - Ke, Wei; Ji, Jie; Zhang, Chengyan; Xie, Hao; Tang, Yayun; Wang, Chuyao
Abstract: Combining phase change materials (PCMs) with building envelope is a promising technology to increase indoor thermal comfort and decrease building energy consumption. However, most existing researches investigated on the PCM layer position in the building envelope only focused on the thermal effects. In this current work, three types of PV-Trombe wall systems with a PCM layer (PCM-PVTW) at different positions were proposed and the coupled impacts on the system's electrical and thermal performance were analyzed compared to the PVTW through numerical analysis based on the electrical and thermal energy outputs trade-off. A comparison case study of these wall systems was conducted under the three full days' ambient conditions in Hefei. Comprehensive performance of these systems in four selected cities in a typical winter week were investigated and the optimal PCM layer position was discussed. Main conclusions are: (1) The PVTW system with a PCM layer attached on the back surface of absorber (APCM-PVTW) achieved the best electrical performance but poorest passive space heating performance; (2) The PCM layer thickness has the greatest impact on the APCM-PVTW; (3) For the colder regions, it's better to place the PCM layer closer to the room side for a better comprehensive benefits. Highlights: Three different types of PV-Trombe wall integrated with a PCM layer were proposed. Mathematical model of the newly proposed system is established and validated. Case study was conducted to compare their comprehensive performance. Positional effects of each PCM-PVTW were analyzed in different climatic cities.